Objects outline delineation by nonliniear filtration methods for boundary pixels - D. V. Zaerko; V. A. Lipnitski; N. L. Bobrova; Dm. V. Zaerko (Системный анализ и прикладная информатика)
A processing of border pixel from pixel map originate problem while work with outline objects segmentation algorithm on bitmap images, which are based on 2D convolution operation. The problem correspond with addition set of pixels which are outside pixel matrix border of processing image. This problem is actual also in other algorithms, which have a common feature – 2D convolution operation. The level of importance are defined by multi used nonlinear filters to border pixels and then union a few images without distortions at the boundaries. The existing methods of pixel set redefining on pre processing step are primitive and affects on subsequent stages of processing. This affects exist between methods of redefining border pixels and algorithms of outline objects segmentation: Sharra, Pruitta, Sobel. The object of investigation is pixel map of halftone image. The subject of investigation is relation assessment between algorithms of outline objects segmentation with methods redefining border pixels. The main target is describing of features special methods to redefining border pixels which positively affecting the subsequent evaluation of the responses for this pixels by algorithms of outline objects segmentation. Analysis, the influence of the algorithm for the outline objects segmentation on the boundary pixels from the preliminary selection of methods of redefinition is carried out by example of combining several satellite images along the outline of urban infrastructure. For simplicity and by necessary of large data volume visualization (pixel half tone matrix size) presented graphs: halftone codes for redefining and border pixels, pixels requests for the algorithm of outline objects segmentation. By analysis criteria and characteristics of an effective method of redefining boundary pixels are described with correspond affects on algorithms of outline objects segmentation on bitmap images.